A Study of ATM Users' Attitude About ATM Receipt in Dindigul City (With Special Reference to Thermal Paper (BPA)) - Sukumar, S.; Begam, S. Samitha (Journal of Commerce and Trade, 2017)
In recent trend the banking sector provides more services to their customers due to the technological development. ATM centre is also one of the major service which are provided by the bankers. The receipt which is issued by machine creates some health issues to ATM users, Most of the receipts contain high levels of the chemical BPA (Bisphenol A), which acts like a hormone and can cause birth defects and cancer including store receipt and fast food receipts, airline tickets, ATM receipts, and other thermal papers in which massive amounts of BPA on the surface of the paper.The investigation says the chemical coating that exists on the paper, which is also used extensively in malls, petrol pumps, bus tickets and online lotteries, can cause far-reaching harm to the health of user. The present study highlight the level and effect of using ATM receipt and users attitude toward receipt of ATM machine in Dindigul city. The study has been undertaken mainly to assess the effect of using receipt and how much cost will be reduced from the avoidance of using receipt and to analyse the socio economic factors, influencing the ATM's user Attitude. The receipt user base increasing every day in updated technology market. The research is conducted for examining the awareness of operation methods, effects of using thermal papers, cost of the papers, number of transactions involved per day and the like.